2019
DOI: 10.1097/md.0000000000016157
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of fascia iliaca compartment block for pain control after hip fracture

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
32
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 28 publications
4
32
2
Order By: Relevance
“…Although almost a decade has passed since the first description of FICB [ 15 ], reports on its applicability for elective total posterolateral hip replacement are still sparse. Furthermore, most of the available studies and meta-analyses concern mainly trauma patients, in whom the use of FICB reduces pain intensity, the need for opioids, and the rates of complications arising from their systemic use [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although almost a decade has passed since the first description of FICB [ 15 ], reports on its applicability for elective total posterolateral hip replacement are still sparse. Furthermore, most of the available studies and meta-analyses concern mainly trauma patients, in whom the use of FICB reduces pain intensity, the need for opioids, and the rates of complications arising from their systemic use [ 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, they only included 5 RCTs for meta-analysis. Hong et al [ 22 ] suggested that FICB has a beneficial role in reducing pain intensity and morphine consumption after hip fracture than the control group. Current meta-analysis has shown that FICB has an equivalent pain control in hip and knee surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…It is also approved for the treatment of acute pain in fracture and burn patients admitted to the facility. FICB appeared to be an effective and relatively safe adjunct to perioperative pain management of femoral and hip fractures, according to a systematic review and meta-analysis research [ [21] , [22] , [23] ]. FICB is used for preoperative, intraoperative, and postoperative analgesia after femur, knee, and hip fractures or surgery.…”
Section: Discussionmentioning
confidence: 99%